Improving Convergence and Aggregation in National Ecosystem Accounting - Bordt, Michael (Université d'Ottawa / University of Ottawa, 2017)
The Sustainable Development Goals (SDGs) express the commitment of countries to integrate ecosystem and biodiversity values into national planning. The System of Environmental-Economic Accounting – Experimental Ecosystem Accounting (SEEA-EEA) is an emerging international standard measurement framework for national ecosystem accounting. The international official statistics community proposes the SEEA-EEA as a means of integrating ecosystem and biodiversity values into national planning by providing guidance on measuring ecosystems and their contribution to the economy. Implementation of such a common measurement framework requires agreement among diverse ethical perspectives, disciplines, national contexts and roles on what to measure, how to measure it and how to interpret those measures to support a common policy direction. This thesis asks the question: If the aim is to provide guidance to countries on integrating ecosystem and biodiversity values into national planning, how could one foster convergence on a common national ecosystem accounting framework that is sufficiently comprehensive to capture the important linkages between ecosystems and human well-being, sufficiently convergent to be accepted by diverse perspectives, sufficiently rigorous for national official statistics, sufficiently consistent to allow for time-series and international comparisons and sufficiently feasible to be affordable for national governments to implement and maintain? To address this broader question, this thesis investigates the sources of divergence in national ecosystem accounting and develops tools to assess and to foster convergence. To accomplish this, I focussed on the following four research questions in four separate papers: 1. How should we think about ecosystem measurement if the aim is comprehensiveness, practicality, and convergence? [Chapter 2] This ethical analysis concludes that for ecosystem accounting to be universal, it needs to explicitly and simultaneously address broad human values, long time-frames, and the concepts of Critical Natural Capital and precaution. 2. What approaches to ecosystem accounting have already been developed and are they sufficient? [Chapter 3] This review of 16 state-of-the-art frameworks finds that none addresses all requirements for convergence on a common national ecosystem accounting framework. Collectively, they provide insufficient guidance on ecosystem classification, measurement in general, delineating Critical Natural Capital, incorporating broad human values and measuring statistical uncertainty. 3. Where is the divergence of values and preferences within the broader community of practice (researchers, users, analysts)? [Chapter 4] This cluster analysis of a survey of 131 expert stakeholders in national ecosystem accounting revealed agreement on the need for broadening the scope, addressing multiple decision contexts and furthering the development of national ecosystem accounting. The most important divergence issues in this community of practice were attributed to different ethical perspectives and differences in interpretation of core concepts. 4. Are current classifications of ecosystems and ecosystem services sufficient for national ecosystem accounting? [Chapter 5] This meta-analysis integrates nine comprehensive ecosystem assessments. It concludes that the lack of rigour in current classifications impedes consensus on aggregating information on “Which ecosystems produce which services?” and therefore current approaches are insufficient for national ecosystem accounting. I suggest an improved ecosystem classification for future studies. In the concluding chapter, I present a synthesis of research arguments and findings of the previous four chapters. The main outcome of this research has been not only the specific findings of the individual chapters, but also the development of a normative and empirically-supported toolkit to improve convergence and aggregation in future national ecosystem accounting frameworks: - Four normative criteria to assess frameworks and to incorporate into future designs and revisions, - A critical comparative assessment of current frameworks, - An empirically supported analysis of the preferences of the community of practice, and - A systematic approach for determining priority ecosystems and services for national ecosystem accounting. This thesis concludes that national ecosystem accounting can be a valuable tool for national planning. The approaches suggested can be applied to establishing a constructive national dialogue on national environmental priorities, to provide evidence to inform those priorities and to apply this evidence to support common policy platforms. However, care must be taken in its implementation to minimize the inherent risks of oversimplification and homogenization of the diverse stakeholder and scientific perspectives.
Keywords: Environmental statistics; Measurement frameworks; Ecology; Environmental-economic accounting